The role of an effective grievance procedure in creating tolerable employment in the South African Police Services - Arie, Motlogelwa Harold (Institute of Development and Labour Law, 2016)
In many instances, the South African Constitution is been seen as the most advanced constitutions in the world. Section 196(4)(f)(ii) of the Constitution has made provision for the Public Service Commission(PSC) to investigate grievances of employees in the Public Services and furthermore to recommend appropriate remedies. However, there is a contradiction when implementing these procedures, as the PSC tends to follow their own set of guidelines with regard to the relevant procedures to be followed when dealing with grievances. Due to this, the public servant [s] rights are been under minded and they seem to lose all confidence and faith with the system. The individual have the potential of resolving the differences that exist amongst them, if it is based on the honest and transparent manner. As mentioned above, even though it is the duty of the PSC to implement the proper grievance procedure at work, its fairness and objectivity will be tested and discuss further in detail in this research. However, in the South African Police Services, due to the nature of their protocol which emphasised on the seniority dominated by rank structure, creates an environment of inequality. Meaning that junior officers are not encourage to challenge their superior on the hostile treatment as it will be viewed as a lack of discipline on the part of the junior officer. The grievance procedure therefore, serves as the formal vehicle which the union will encourage the employee to follow in seeking for justice against unfair treatment. In most case the employee are sceptical to file a grievance against their seniors, for fear of victimization, however, this might worsen the situation if it was not brought to the attention of the management. On many occasions the employees have rather taken a decision to resign due to pressure from the management. In terms of section 186(1)(e) of the Labour Relations Act, continued employment are made intolerable if the discontent experience by the employees becomes more and more imminent in the work environment. In a situation where the continued employment has become intolerable, the employee can claim constructive dismissal. This research looks at the different ways which the courts arrive at, when deciding on cases from the South African legal system, in order to determine which tests to apply when dealing with constructive dismissal.